Study of capacitance effect for dual open circuit band-stop resonator / Ahmad Amzar Abd Rashid - Abd Rashid, Ahmad Amzar (2011)
Microstrip Dual Open Circuit Stub filters is fabricated using FR4 substrate to investigate the effect of capacitance in series with the resonator stub. The FR4 substrate thickness is 1.6mm and has a relative dielectric constant of 5.4. The capacitance is added at the resonator open ends such as to tune the Dual series stub filter from 2GHz frequency to 1.36GHz frequency. It is known that to see the effect of shifting, the electrical length of the resonator is being altered from its original value. Different values of capacitors are simulated with the dual open circuit stub filter design to see the effect shifting to the left of the Sn value. Frequency are practically shifted from right to left with increasing the value of capacitor and the suitable value is selected for measurement. From the project, the tuning percentage achieved is 32%. Thus, it shows better selectivity can be achieved by the designer to obtained different centre frequencies for other uses.